2012
DOI: 10.1002/clen.201200107
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Acid Pharmaceuticals in the UV/H2O2 Process: Effects of Humic Acid and Inorganic Salts

Abstract: The presence of acid pharmaceuticals in water environments poses a potential threat to ecosystems and human health. Recent research has shown that photo oxidation processes are much more effective for removing these pharmaceuticals. However, the existence of humic acid (HA) could inhibit the clearance efficiency of this process. In this study, we investigated the photochemical degradation of six selected acid pharmaceuticals in surface water and effluent from wastewater treatment plants using the UV/H 2 O 2 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…The reactive OPEs were removed by more than 90% in the first 10 min (H 2 O 2 consumption = 2.3 mg L À1 ); while after 1 h reaction, the recalcitrant TCPP, TDCP, TCEP and TEHP were only removed by 72%, 53%, 61% and 65%, respectively. On the one hand, UV irradiation of HA may produce Å OH and other secondary oxidants to enhance the removal of organic pollutants [30]; on the other hand, the removal of organic pollutants may be inhibited because HA competes for not only UV light against H 2 O 2 but also Å OH against target pollutants [15,31]. In this study, the inhibitory effect of HA seemed to dominate in the degradation of target OPEs by UV/H 2 O 2 .…”
Section: Uv/h 2 O 2 Treatmentmentioning
confidence: 66%
See 1 more Smart Citation
“…The reactive OPEs were removed by more than 90% in the first 10 min (H 2 O 2 consumption = 2.3 mg L À1 ); while after 1 h reaction, the recalcitrant TCPP, TDCP, TCEP and TEHP were only removed by 72%, 53%, 61% and 65%, respectively. On the one hand, UV irradiation of HA may produce Å OH and other secondary oxidants to enhance the removal of organic pollutants [30]; on the other hand, the removal of organic pollutants may be inhibited because HA competes for not only UV light against H 2 O 2 but also Å OH against target pollutants [15,31]. In this study, the inhibitory effect of HA seemed to dominate in the degradation of target OPEs by UV/H 2 O 2 .…”
Section: Uv/h 2 O 2 Treatmentmentioning
confidence: 66%
“…Compared with other advanced treatments such as Fenton's regent oxidation, membrane filtration and activated carbon adsorption, ozone and UV/H 2 O 2 have no requirement for pH adjustment, sludge disposal, membrane backwash, or adsorbent regeneration, thus are commonly applied for water and wastewater treatment [12,14]. In addition, water matrix, especially the type and content of natural organic or inorganic matter, can affect the oxidation of organic pollutants by competing for the oxidant and/or affecting the generation of Å OH [15][16][17]. However, there is little research concerning the effect of water matrix on the removal of OPEs in ozone and UV/H 2 O 2 treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The possible reason could be the higher reaction priority of these DOM extracts with PS than FLU. Similarly, Yuan et al (2013) also reported this phenomenon during aqueous degradation of ibuprofen by UV/H 2 O 2 process with the addition of 10 mg/L humic acid. …”
Section: Ps Oxidation Of Flu By Common Activation Methodsmentioning
confidence: 88%
“…The methods are limited by a few drawbacks; the drawback of the biological method is the longer retention time, usually measured in days, to oxidize the organic compounds, the adsorption method cannot mineralize the pollutants and the electrochemical method generates the new toxic intermediates . On the other hand, advanced oxidation processes (AOPs) mineralize the organics to harmless final products using stable and non‐toxic photocatalysts, suitable reaction time, appropriate irradiation wavelength at ordinary temperature and atmospheric pressure . The mineralization is carried out on the photocatalyst surface by hydroxyl radicals ( • OH) that are powerful and non‐selective to oxide pollutants and probable intermediates .…”
Section: Introductionmentioning
confidence: 99%